Engineering the next-generation of CAR T-cells with CRISPR-Cas9 gene editing - Dimitri, Alexander; Herbst, Friederike; Fraietta, Joseph A. (Molecular cancer, 2022)
Chimeric Antigen Receptor (CAR) T-cells represent a breakthrough in personalized cancer therapy. In this strategy, synthetic receptors comprised of antigen recognition, signaling, and costimulatory domains are used to reprogram T-cells to target tumor cells for destruction. Despite the success of this approach in refractory B-cell malignancies, optimal potency of CAR T-cell therapy for many other cancers, particularly solid tumors, has not been achieved. Factors such as T-cell exhaustion, lack of CAR T-cell persistence, cytokine-related toxicities, and bottlenecks in the manufacturing of autologous products have hampered the safety, effectiveness, and availability of this approach. With the ease and accessibility of CRISPR-Cas9-based gene editing, it is possible to address many of these limitations. Accordingly, current research efforts focus on precision engineering of CAR T-cells with conventional CRISPR-Cas9 systems or novel editors that can install desired genetic changes with or without introduction of a double-stranded break (DSB) into the genome. These tools and strategies can be directly applied to targeting negative regulators of T-cell function, directing therapeutic transgenes to specific genomic loci, and generating reproducibly safe and potent allogeneic universal CAR T-cell products for on-demand cancer immunotherapy. This review evaluates several of the ongoing and future directions of combining next-generation CRISPR-Cas9 gene editing with synthetic biology to optimize CAR T-cell therapy for future clinical trials toward the establishment of a new cancer treatment paradigm.